Ontological and Axiological Criteria of Organising Help for the Disabled in the Philosophy of Ju?rgen Habermas - Pezdek, Krzysztof (INSTED: Interdisciplinary Studies in Education & Society, 2012)
The article presents ontological and axiological criteria of organising help for the disabled. The basis for the examination is the concept of Ju?rgen Habermas? communication activity. What results from the research I have conducted is that while organising the help it is essential to establish the extent of rationality and self-awareness of the disabled in need. It allows to specify the axiological hierarchy of existences, needs, aspirations, targets, etc. adopted by them. Therefore the disabled people should be provided with a chance of a free and fair discourse with particular members of society. However, first, it is necessary to prepare them appropriately for the participation in the discourse, both meritorically and normatively.